A volkswagen Kombi: expressão de cultura e de relações com a sociedade pela visão do design estratégico - Arnt, Carlos Antônio de Andrade (Universidade do Vale do Rio dos Sinos, 2016)
The purpose of the study is to contribute with project processes that involve the connections of products and brands to society, culture and market. The object of the research is the Volkswagen Bus (Van, Kombi), an iconic vehicle in the automobile market with an unique history that surpasses the commonly established boundaries for a car and its functions, promoting a reflection from the investigation of the manifested bonds and suggesting the development of scenarios that corroborate for the illustration of the importance of this vehicle. The area of Strategic Design will be used as base of knowledge through the application of its theoretical references and disciplines. Along with these objectives, important elements for the comprehension of the connections between products and brands are added: affection and memory that people take from experience and the importance to perpetuate cases as this one, of products that establish very close relations to their users and of the universe they live in. The social connections that the Volkswagen Bus built, involuntarily, are considered and explored approaching the different manifestations that social groups, along six decades, connected to the Bus and inserted them in everyday life, be it as a common vehicle or as a platform for their constructions. The theoretical references of Strategic Design, the backbone of this study, will corroborate to explain the assumptions, contributing through a meta-project, multidisciplinary and cultural view for the reading and understanding of the established relationship nets between the Volkswagen Bus and its users and admirers. Starting from the assumption that the project of the product was developed with the primary function of cargo, and eventually people, transportation, the vehicle will be analyzed through a case study, methodology that is most adequate since that the maker and the market are as important as the Bus for contemplation on the subject matter. With all of the information, bibliography, documentation, deep interviewing and testing of a sample group, it was possible to understand the universe of the Volkswagen Bus, to project scenarios and to suggest future action for the memory of the vehicle.
Keywords: Design estratégico; Kombi; Cultura; Sociedade; Memória; Strategic design; Volkswagen; Bus; Van; Kombi; Culture; Society; Memory; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial